The Development Of Physical Activity Model Through A Circuit Game To Develop The Basic Locomotor Movement Ability For Earlier Elementary Student - Yudanto Yudanto; Kristi Utami (UNIB Press, 2021)
This research aims to produce a product of a physical activity model through a circuit game to develop the basic locomotor movement ability for an earlier elementary student. This research is development research. The procedures or steps that were used in this study, namely: 1 ) analyzing the product, 2) developing the initial product, 3) expert validation and product reliability testing, 4) small and wide-scale trials, 5) revisions products, 6) organizing of the final product. The validation test was using content validation and the reliability was using the Crude Index Agreement, the results of the reliability test obtain a coefficient of 0.75-0.81. The small-scale trials were conducted at SD Negeri Karangjati and the large-scale trials were conducted at SD Negeri Mlesen and MI Husnayain Sleman. The final results in this research is a physical activity model through a circuit game consisting of 1) preparing places and equipment, 2) initial/warming up activities, 3) Core Activities consisting of 5 posts games namely Lampu Lalu Lintas, Topi Kerucutku, Balap Engklek, Tongkat Berjalan, and Terowongan Bola, 4) closing activities/cooling down.